Multimodal Fake News Detection with Contrastive Learning and Optimal Transport - Shen, Xiaorong; Huang, Maowei; Hu, Zheng; Cai, Shimin; Zhou, Tao (Frontiers in Computer Science, 2024)
IntroductionThe proliferation of social media platforms has facilitated the spread of fake news, posing significant risks to public perception and societal stability. Existing methods for multimodal fake news detection have made important progress in combining textual and visual information but still face challenges in effectively aligning and merging these different types of data. These challenges often result in incomplete or inaccurate feature representations, thereby limiting overall performance.MethodsTo address these limitations, we propose a novel framework named MCOT (Multimodal Fake News Detection with Contrastive Learning and Optimal Transport). MCOT integrates textual and visual information through three key components: cross-modal attention mechanism, contrastive learning, and optimal transport. Specifically, we first use cross-modal attention mechanism to enhance the interaction between text and image features. Then, we employ contrastive learning to align related embeddings while distinguishing unrelated pairs, and we apply optimal transport to refine the alignment of feature distributions across modalities.ResultsThis integrated approach results in more precise and robust feature representations, thus enhancing detection accuracy. Experimental results on two public datasets demonstrate that the proposed MCOT outperforms state-of-the-art methods.DiscussionOur future work will focus on improving its generalization and expanding its capabilities to additional modalities.